Analisis Komparatif Abnormal Return dan Trading Volume Activity Emiten Sektor Mining Berdasarkan Pengumuman Kasus Pasien Covid-19 Pertama di Indonesia - Akhadiyah, Lailatul; Isbanah, Yuyun (Jurnal Ilmu Manajemen, 2021)
On March 2nd 2020, the first case of Covid-19 was found in Indonesia. The purpose of this research is to analyze the reaction of the Indonesian capital market to the first case of Covid-19 using average abnormal return (AAR), cumulative abnormal return (CAR), and trading volume activity (TVA) before and after the event. The observation began seven days before and seven days after that event. The population of this research uses the data of mining sector companies listed in February and March 2020 on the BEI. The sampling technique used is purposive sampling with a total of 41 mining companies. This study uses quantitative research and the comparative method—the research testing by Wilcoxon Signes Rank Test. The result showed no differences in AAR, CAR, and TVA of mining sectors between before and after the announcement of the first cases of Covid-19. Investors are expected to be more careful in making investment decisions because this pandemic has occurred for a long time and around the world.